2020
DOI: 10.1158/0008-5472.can-19-2288
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Cell–Derived Soluble CD44 Promotes Tumor Progression by Triggering Macrophage IL1β Production

Abstract: IL1b is a central regulator of systemic inflammatory response in breast cancer, but the precise regulatory mechanisms that dictate the overproduction of IL1b are largely unsolved. Here, we show that IL1b secretion is increased by the coculture of human monocyte-like cells and triple-negative breast cancer (TNBC) cells. In addition, macrophages robustly produced IL1b when exposed to the conditioned media of TNBC cells. Consistent with these observations, macrophage depletion decreased serum IL1b and reduced bre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 53 publications
3
45
0
Order By: Relevance
“…This pathway plays a major role in tumor lymphangiogenesis, murine lymph node, and lung metastasis, while NLRP3 expression is correlated with human mammary carcinoma development [ 140 , 141 ]. Similarly, murine 4T1 breast cancer cells release soluble CD44, which in turn induces macrophage-mediated IL-1β production, leading to tumor growth and lung metastases [ 142 ]. Human lung cancer cells release microparticles that bind TLR3 to trigger NLRP3 inflammasome pathways in macrophages and IL-1β secretion.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…This pathway plays a major role in tumor lymphangiogenesis, murine lymph node, and lung metastasis, while NLRP3 expression is correlated with human mammary carcinoma development [ 140 , 141 ]. Similarly, murine 4T1 breast cancer cells release soluble CD44, which in turn induces macrophage-mediated IL-1β production, leading to tumor growth and lung metastases [ 142 ]. Human lung cancer cells release microparticles that bind TLR3 to trigger NLRP3 inflammasome pathways in macrophages and IL-1β secretion.…”
Section: Pro-and Anti-tumor Effects Of Il-1βmentioning
confidence: 99%
“…In addition, breast cancer patients show highly increased serum levels of IL-1β which is dependent on tumor stage 18,19 . This elevated expression of IL-1β is more likely to be associated with establishment of inflammatory tumor microenvironment and breast cancer progression 18,[20][21][22] . Further, significant correlation was noticed between IL-1β expression and subsequent development of metastasis 23,24 .…”
Section: Involvement Of the Inflammasomes And Their Effector Moleculementioning
confidence: 99%
“…Salivary and plasmatic detection of sCD44 have been evaluated as potential diagnostic biomarkers for head and neck cancer, but the conclusions are inconsistent [27][28][29]. Finally, preclinical studies suggested that sCD44 may be secreted by tumor cells in triple negative breast cancer and could play a critical role in tumor growth [30]. As the indications for immunotherapies, particularly anti-PD1, are increasing, the need for a reliable biomarker predictive of response has become critical.…”
Section: Introductionmentioning
confidence: 99%